2002
DOI: 10.1080/019262302753559533
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Mucosal Necrosis in Male CD Rats Following Acute Inhalation Exposure to Hydrogen Sulfide: Reversibility and the Possible Role of Regional Metabolism

Abstract: Hydrogen sulfide (H2S) is a potent inhibitor of cytochrome oxidase (CO) and is associated with dysosmia and anosmia in humans and nasal lesions in exposed rodents. An improved understanding of the pathogenesis of these lesions is needed to determine their toxicological relevance. We exposed 10-week-old male CD rats to 0, 30, 80, 200, or 400 ppm H2S for 3 hours/day for 1 or 5 days consecutively. The nose was histologically examined 24 hours after H2S exposure, and lesion recovery was assessed at 2 and 6 weeks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
(24 reference statements)
3
31
0
1
Order By: Relevance
“…H 2 S treatment has also been shown to lead to nasal lesions and olfactory epithelial necrosis (11). On the other hand, H 2 S induces serum-independent cell cycle entry in rat intestinal epithelial cells and increases the fraction of colonic mucosa cells in the S phase (12,13).…”
mentioning
confidence: 99%
“…H 2 S treatment has also been shown to lead to nasal lesions and olfactory epithelial necrosis (11). On the other hand, H 2 S induces serum-independent cell cycle entry in rat intestinal epithelial cells and increases the fraction of colonic mucosa cells in the S phase (12,13).…”
mentioning
confidence: 99%
“…Apoptosis in various tissues caused by antimicrotubule agents including VCR, vinblastine sulfate (VBL), vindesine sulfate (VDS), and paclitaxel (PTX) is a very complex process associated with many protein kinase signaling pathway, and it is supposed that phosphorylation of bcl-2 and elevations of p53 and p21 lead to apoptosis (Wang et al, 1999). In another aspect, the susceptibility of local tissues to xenobiotics has been reported to sometimes differ from site-to-site in the olfactory epithelium, and to be related to site-specific metabolism that can also play a crucial role in the tissue concentration of the parent compound or toxic metabolites (Morgan, 1994;Cleton, 1995;Brenneman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The previous experimental studies on rats and human revealed a role of H 2 S on the living cells. A study on experimental rats, H 2 S inhalation was found to have a severe cytotoxic effect on the nasal epithelium [6] and olfactory epithelial necrosis and sloughing [7]. In human studies, H 2 S was also found to have a dose-dependent intensification of cell death via apoptosis and necrosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…The same mechanism may cause pharyngeal soreness, gingivitis, rhinitis, and eyes irritation. On chronic exposure, this also might cause gingival and periodontal disease among people who work in environment with presence of H 2 S. Acute, subchronic, and prolong exposure to H 2 S might also cause neuronal olfactory damage, loss of smell sensation, and rhinitis which was reported in previous studies on human, rats, and mice [4,7,14,15]. At lower concentrations, H 2 S was found to cause eye mucosal irritation, and keratoconjunctivitis called 'gas eye', and at higher concentrations there was risk of pulmonary edema [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation